Compact and non compact structures of the phi-four equation. Issue 1 (2nd January 2017) - Inc, Mustafa; Kilic, Bulent
Abstract: In this paper, we establish exact special solutions of the phi-four equation. We use the reduction of order method and the He's variational principle for this equation. So, we get general formulae for the compacton, solitary pattern, soliton, and periodic solutions.